Spatial mathematics theory and practice through mapping - Arlinghaus, Sandra L. (CRC Press, 2013)
"Spatial mathematics and analysis, two different approaches to scholarship, yield different results and employ different tools. This book explores both approaches to looking at real world issues that have mathematics as a critical, but often unseen, component. Readers learn the mathematics required to consider the broad problem at hand, rather than learning mathematics according to the determination of a (perhaps) artificial curriculum. This format motivates readers to explore diverse realms in the worlds for geography and mathematics and in their interfaces. Written by a field leader in education involving mathematics and mapping software and a field leader in mathematical geography. Supplies robust material and exercises tested in workshop situations . Includes software to which exercises are geared. Explains and includes QR (quick response) codes that link text to downloads server. Focuses on detailed illustrations of mathematical backgrounds in GIS with an interdisciplinary interaction"--